Geotouristic aspects of the Geopark Cabo de Gata-Níjar (Andalusia, Spain) - Lorenc, Marek W.; Janusz, Małgorzata (Geotourism/Geoturystyka, 2020)
The Cabo de Gata-Níjar Geopark is one of the most remarkable examples of the geological heritage in Spain, and it comprises the largest volcanic massif in Andalusia. It is built of andesites and dacites with such typical volcanic forms like lava flows, volcanic calderas, volcanic domes and columnar joints. The ancient beaches and reefs demonstrate the presence of climate change as well as of a subtropical sea. The tourism in this region is mainly focused on its beaches and some remains of the cultural heritage, like salt works or the Rodalquilar gold mine. This study pretends to analyze the reasons and consequences of this matter. Highlighting the good state of preservation of this area and the possibility of enjoyment of its beauty, more attention should be paid to the popularization of the local geological aspects, which would significantly increase the awareness and interest among the tourists.